Self-esteem in Fatherless Adolescent is reviewed by Parental Attachment and Peer Relationship - Dwianti, Silvi; Riza, Wina Lova; Aisha, Dinda (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The family is the smallest social unit in society that includes a father, mother, and children who are characterized by living together. However, not all families live with fathers due to the loss of fathers (death), divorced parents, this is called fatherless. This study was conducted to determine the effect of parental attachment and peer relationships on self-esteem in fatherless adolescents in Karawang Regency. The population studied was fatherless adolescents aged 12-21 years who live in Karawang Regency. Therefore, the sampling technique used was non-probability sampling through snowball sampling technique, the number of respondents in this study were 193 respondents. The measuring instruments used were the IPPA (Inventory of Parent and Peer Attachment) scale, CA-PRS (Children Adolescent Peer Relationship Scale) and RSES (Rosenberg Self-esteem Scale). The methods applied are normality test, linearity test, and multiple regression analysis. The results showed a significance value of 0.001 <0.05, which means that there is an influence of parental attachment and peer relationships on self-esteem in fatherless adolescents in Karawang Regency. The test results of the coefficient of determination with R Square 0.075. Therefore, the amount of influence of parental attachment and peer relationship together on self-esteem is 7,5%.Keluarga dianggap sebagai unit sosial terkecil dalam lingkungan masyarakat yang mencakup ayah, ibu, serta anak yang memiliki ciri khas seperti tinggal bersama. Namun, tidak semua keluarga tinggal bersama ayah yang disebabkan kehilangan ayah (meninggal), orang tua bercerai hal ini disebut dengan fatherless. Penelitian ini dilakukan guna mengetahui pengaruh kelekatan orang tua dan peer relationship terhadap self-esteem pada remaja fatherless di Kabupaten Karawang. Populasi yang diteliti yaitu remaja fatherless yang berumur 12-21 tahun yang berdomisili di Kabupaten Karawang. Oleh karena itu, teknik pengambilan sampel yang digunakan yaitu non-probability sampling melalui teknik sampel snowball sampling, jumlah responden dalam penelitian ini adalah 193 responden. Alat ukur yang digunakan skala IPPA (Inventory of Parent and Peer Attachment), CA-PRS (Children Adolescent Peer Relationship Scale) dan RSES (Rosenberg Self-esteem Scale). Metode yang diterapkan yaitu uji normalitas, uji linearitas, serta analisis regresi berganda. Hasil penelitian menunjukkan nilai signifikansi yaitu 0,001 < 0,05 yang berarti ada pengaruh kelekatan orang tua dan peer relationship terhadap self-esteem pada remaja fatherless di Kabupaten Karawang. Hasil uji koefisien determinasi dengan R Square 0,075. Oleh karena itu, besaran pengaruh kelekatan orang tua dan peer relationship secara bersama-sama terhadap self-esteem yaitu sebesar 7,5%.